CLIMA LABORAL DE LOS SOCIOS DE LA COOPERATIVA DE TAXIS DE CALUMA - Morales Vera, Marcia Odalis (2018)
Currently, leaders and managers of organizations can not fail to recognize that to meet the purposes and purposes of their organizations is highly relevant to take into account the variables of work climate, because these relate to job satisfaction, is therefore, the need arises to understand the behavior of the work environment and how it is perceived by a collaborator, in this sense the relationship between worker and employer is shown as the reasons that allow individuals to develop their work tasks. Correct way and with greater commitment according to the needs of the company and society.